PERSEPSI PETERNAK SAPI TERHADAP PELAKSANAAN INSEMINASI BUATAN DI DESA GUNUNG PUTIH KECAMATAN TANJUNG PALAS KABUPATEN BULUNGAN - Ramadhana, Arya Pitra; Ibrahim, Ibrahim; Ismanto, Arif (Jurnal Peternakan Lingkungan Tropis, 2022)
The purpose of this study was to determine the perception of cattle farmers on the implementation of artificial insemination in Gunung Putih Village, Tanjung Palas District, Bulungan Regency. The analysis used in this study is to use a Liker scale. This research was conducted from May to June 2022 in Gunung Putih Village, Tanjung Palas District, Bulungan Regency. This type of research is a type of descriptive research. The results of this study indicate that the perception of cattle farmers on the implementation of artificial insemination in Gunung Putih Village, Tanjung Palas District, Bulungan Regency mostly agrees with the implementation of artificial insemination because it helps farmers in breeding livestock for breeders.